Effect of under nitrogen annealing on photo-electrochemical characteristics of films deposited from authentic Cu2SnSe3 sources by thermal vacuum under argon gas condensation - Sabli, Nordin; Talib, Zainal Abidin; Hilal, Hikmat S. (Elsevier, 2017)
This communication describes how annealing under nitrogen affects photo-electrochemical characteristics of films deposited from authentic Cu2SnSe3 sources by vacuum evaporation under argon gas (low flow rate 5 cm3/min) using substrate 300 °C. Annealing lowered the photoresponse of the deposited film, by affecting crystallite structure, morphology, composition and pores in the films. Annealing at temperatures in the range 150–350 °C improved crystallinity of the film but lead to pore formation between adjacent, which lowered photoresponse by increased resistance across the electrode/redox interface. Higher temperature (450 °C) annealing lead to SnO2 formation, as an additional phase, at the expense of Cu2SnS3 decomposition. Porosity and mixed phases with SnO2 presumably increased film internal resistance and resulted in poor charge transfer across the solid/redox couple interface. By affecting film characteristics, annealing lowered photoresponse for the deposited films.